The role of intermediate inputs in a multisectoral balance-of-payments-constrained growth model: The case of Mexico - Ricardo Azevedo Araújo; Matheus Silva de Paiva; Júlio Fernando Costa Santos (Journal of Economic Structures, 2019)
We focus on the effects of the imports of intermediate inputs over the growth performance. Such an analysis is essential insofar as some countries import large amounts of intermediate inputs to be used in the production of final goods to export. Then it arises the question of whether such a strategy is harmful to the growth performance in a balance-of-payments-constrained growth (BPCG) setup. To address this point, the paper blends the multisectoral BPCG model incorporating structural change (MSTL), by Araujo and Lima (Camb J Econ 31(5):755-774, 2007), and the BPCG model including intermediate goods by Blecker and Ibarra (Struct Change Econ Dyn 25(C):33-47, 2013), and applies the resulting framework to the Mexican economy from 1962 to 2014. The most important result is that the MSTL growth rate in the presence of foreign content of exports is lower than the 'standard' MSTL growth rate calculated in the usual fashion (ignoring intermediate imports). That shows the importance of considering imports of intermediate goods in a BPCG model, at least for countries such as Mexico that rely massively on them. It especially helps to explain the reduction both in the ratio of the income elasticities and the growth rate of the Mexican economy, a result also found by Ibarra (Econ Change Restruct 44:357-368, 2011).
Keywords: 330; Intermediate inputs; Balance-of-payments-constrained growth; Structural change; Mexico